Influence of Second Thermal Cycle on Reheat Cracking Susceptibility of Welding CGHAZ in Vanadium-Modified 2.25Cr1Mo Steel. (2015) - Han, Y.C.; Chen, X.D.; Fan, Z.C.; Bu, H.Q.
Abstract: The welding coarse grained heat affected zones (CGHAZ) of Vanadium-modified (V-mod) 2.25Cr1Mo steel are prone to reheat cracking because of its poor ductility in the temperature range of intermediate stress relief treatment (650∼680 ̊C). Considering the multiple-pass welding procedure of V-mod 2.25Cr1Mo steel, the microstructure, high temperature ductility and reheat cracking susceptibility of the CGHAZ subjected to second welding thermal cycle with different peak temperatures (Tp2 ) were studied by the thermal simulation technique. The results show that the high temperature ductility of double-cycle CGHAZs with all second peak temperature (730 ̊C, 890 ̊C, 1020 ̊C, 1250 ̊C) exhibits recovery in comparison to the single-cycle CGHAZ. Under the condition of Tp2 =890 ̊C and Tp2 =1020 ̊C, the recrystallization of prior austenite grains in CGHAZ results in a remarkable elevation of the high temperature ductility and a significant reduction of the reheat cracking susceptibility.